National policies and the sectoral pattern of economic growth - Headey, Derek D. (Wiley, 2008)
This article presents tests of whether the kinds of “national” policy variables used to explain cross‐country variation in the growth of aggregate GDP per capita can also successfully explain per capita growth in the agricultural and nonagricultural sectors of developing countries. There are four main results of interest. First, relative to nonagriculture, convergence is much slower in agriculture and the burden of population growth is generally much higher. Second, while orthodox economic policies share positive associations with economic growth in the nonagricultural sectors of developing countries, such policies fail to robustly predict variation in agricultural growth. Third, size of government indicators often yield an “unexpected” positive association with agricultural growth. And finally, although there is some evidence that fewer price controls are associated with faster agricultural growth, these associations are statistically quite weak and quantitatively quite small.